Global food safety: determinants are Codex standards and WTO's SPS food safety regulations. Issue 2 (29th July 2014) - Mahajan, Rajneesh; Garg, Suresh; Sharma, P.B.
Abstract : Purpose: – The purpose of this paper is to investigate perspective in explaining how global food safety can be created through stringent implementation of Codex and World Trade Organization (WTOs) Sanitary and Phytosanitary food safety regulations and suggests the appropriate food safety system for India. Design/methodology/approach: – The study has been deployed a survey questionnaire using a sample of Indian Processed food sector. In order to collect data 1, 000 supply chain professional were contacted for seeking their consent to be part of the survey. Whereas total responses collected were 252 from Delhi and NCR, with response rate 25.2 percent. The data collected was empirical tested using descriptive statistics, correlation analysis, regression and ANOVA. Findings: – The results and discussions indicate that all the global food safety norms laid down by WTO such as goods manufacturing practices, good hygienic practice, hazard analysis critical control point, has been developed to embody principles of safe food processing sector globally. India has also developed their food safety norms as per laid down principles by WTO. Originality/value: – The present research work makes an important contribution to the body of literature on global food safety. The paper has important implications for the processed food sector since it tries to bring out practices which would help in successful implementation of global food safety standards. It is useful for academic food research as well as for processed food corporate.